Dívidas d’alma : sensibilidades entre vivos e mortos no sertão do São Francisco, Minas Gerais - Lucas Parreira Álvares (2023)
A folklorist once stated that the backlands of the São Francisco river, in Minas Gerais, “is precisely the center most frequented by souls from another world”. Awaiting their salvation, condemned to expiation, or simply due to unrestricted attachment to matter, souls wander in the air, a local denomination of “purgatory”, this terrain of disputes and negotiations in which both the living seek the dead – an “agency over the souls” – and the dead seek the living – an “agency of souls”. Feeling souls, seeing them, hearing voices, dreaming of the dead, and making a pact with the dead are recurring examples that reify spiritual beings and make them palatable, to the point that the appetites of sensitivity become capable of feeling their presence. Subsidized by field trips to the cities of São Romão, São Francisco and Januária, north of Minas Gerais, between 2021 and 2023, and combined with an in-depth study of works by folklorists, anthropologists, historians and other previous researchers, the objective of this work is to present and compare the relationships, gifts and commitments between the living and the dead in the backlands of São Francisco, Minas Gerais, Brazil. The conclusion obtained is that the moral obligations contained in the relationships of pact and promise, expressions of bargains, cross the threshold between life and death and extend, after the death of those involved, to consequences that move beyond individual domains of the ego. The inclusion of third parties as beneficiaries of the original debts causes a true circuit of obligations between the living and the dead that, in the region, is fed through cultural expressions such as myths, rites, festivals and celebrations.